Community Perceptions of Agricultural Zakat in View of Sharia Economic Law (Leppangeng Village, Belawa District, Wajo Regency) - Andi Muhammad Aidil; Hasanuddin (PT FORMOSA CENDEKIA GLOBAL, 2022)
Agricultural zakat as stipulated in Law Number 23 of 2011 concerning Management of Zakat in Article 4 paragraph (2) states that zakat money includes agricultural and plant assets, forests, agricultural products and plants and forests belonging to individuals. muzaki. Or a business entity whose payment system is regulated according to Islamic law. However, there is still a lack of awareness of farmers about the obligation of zakat on agricultural products, as evidenced by the fact that most of them issue zakat on simple agricultural products (at first glance) without following the provisions regarding the amount of zakat. The research method used is a qualitative descriptive method that aims to determine people's perceptions of agricultural zakat and views of economic law. This research was conducted in Leppangeng Village, Kec. Belawa Regency. Wajo which takes place from 15 December 2021 to 15 February 2022. The results show that the public's perception of agricultural zakat is that 100% of the people who have been interviewed know the law of paying agricultural zakat is obligatory, 89% know the nisab and the percentage of agricultural zakat according to their respective perceptions and only 11% have the same perception as the author about the nisab and the percentage of agricultural zakat. The view of the community's Sharia Economic Law is that the agricultural zakat that has been issued by the community is in accordance with Islamic law in verses and hadiths.